(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Nitrogen (N) requirement of French bean (Phaseolus vulgaris L.) in Bangladesh is not yet determined. The present study has evaluated the performance of French bean varieties and nitrogen rates through a field experiment conducted at the research field of Plant Physiology Section of Horticulture Research Centre, Bangladesh Agricultural Research Institute (BARI) during rabi seasons of 2016- 17 and 2017-18). The experiment was set up with frenchbean varieties BARI Jharshim-1 and BARI Jharshim-2 and N rates viz., 0, 75, 100, 125 and 150 kg N/ha arranged in a randomized complete block design, with three replications. The variety BARI Jharshim-1 treated with 150 kg N/ha produced the highest in respect of shoot dry matter yield (879.65 g/m2), number of pods/plant (29.70), weight of pods/plant (147.20 g) and green pod (marketable) yield of 19.48 t/ha); in contrast, lower yield and yield attribute was obtained with BARI Jharshim-2 with 125 kg N/ha. Pods of both varieties showed appreciable amounts of protein, vitamin-C and vitamin-A when N was fertilized at 125 followed by 150 kg/ha. Bangladesh J. Agril. Res. 46(4): 425-433, December 2021